Decline in mortality from coronary heart disease in Finland from 1969 to 1979. Issue 6381 (11th June 1983) - Salonen, J T; Puska, P; Kottke, T E; Tuomilehto, J; Nissinen, A
Abstract : The trends in mortality from coronary heart disease in the 1970s and the differences in trends between counties within Finland were calculated from official mortality statistics among the population aged 35 to 64 years. During this period coronary mortality declined by a mean of 1.1% for men and 2.3% for women annually in the whole of Finland. A community based cardiovascular control programme was started in 1972 in North Karelia, a county in the east of Finland. The decline in coronary mortality in this county between 1969 and 1979 was 24% in men and 51% in women. The decline in the rest of Finland over the same period was 12% in men and 24% in women. The decline in North Karelia was greater than that in other counties of Finland for both men and women and that difference exceeded random variation, with over 95% likelihood for both sexes. Even with adjustment for rates before 1974 with cross-county multiple regression analyses the difference persisted. Although further studies are needed, the changes in coronary mortality in North Karelia suggest that the preventive programme has been effective.